EMBARAZO TRIPLE: COMPLICACIONES MATERNAS Y PERINATALES - Paolo Ricci A.; Ernesto Perucca P.; Cristián Pérez C.; Danisa González V.; Sergio Valenzuela R.; Isabel Galleguillos F. (Permanyer, 2005)
Objetivo: Revisar las complicaciones maternas y perinatales de los embarazos triples atendidos en el Servicio de Obstetricia del Hospital Barros Luco-Trudeau. Pacientes y Método: Se analizan 11 embarazos triples ocurridos entre enero de 1996 y diciembre de 2004. Resultados: Hubo una incidencia de 1 embarazo triple en 4.730 partos. Dos embarazos fueron resultado de tratamientos de fertilidad. Se registró 1 óbito y 1 muerte (polimalformado) a los 35 días de vida. El parto se resolvió entre las 29+1 y 36+3 semanas de gestación mediante cesárea, en 55% por inicio de trabajo de parto. Se utilizó surfactante pulmonar en 8 de los 32 recién nacidos (25%) y ventilación mecánica en 5 (16%). La complicación materna de mayor frecuencia fue el síndrome hipertensivo del embarazo (50%), dos preeclampsias y un síndrome de Hellp. La utilización de días cama por los recién nacidos fue de 822 días para 32 casos (mediana: 21 días; rango: 6-64 días). El total de días cama utilizados por las 11 gestantes fue 270 días, con promedio de 25 días. Conclusión: Aún cuando se registraron buenos resultados perinatales, los embarazos triples se asocian a mayor morbilidad materna y perinatal. Además producen un mayor gasto de recursos de neonatología, especialmente debido a prematurez Objective: To review the maternal and perinatal complications of the triplet pregnancies registered in our service. Patients and Method: We analyzed 11 triplet pregnancies with an incidence of 1 in 4,730 childbirths, between January 1996 to December 2004. Results: Two pregnancies were been from fertility treatments. There was only 1 stillbirth and 1 death to 35 days of birth (multiple malformations). The childbirth was resolved between the 29+1 and 36+3 weeks of gestation. The resolution was by caesarean section, in 55% for labor. Pulmonary surfactante was necessary to use in 8 of the 32 new born (25%), and mechanical ventilation in 5 (16%). The maternal complication of greater frequency was hypertensive syndrome of the pregnancy appearing in 50% of the cases, 2 preeclampsia and one Hellp syndrome. The use of bed-days by new born was 822 days for 32 cases, (median 28 days; rank: 6-64 days). The total bed-days used by the 11 pregnant were 270 days, with an average of 25 bed-days. Conclusion: Even though in our casuistry good perinatal results were registered, triplet pregnancies are associated to greater maternal and perinatal morbidity. In addition they produce a greater cost of neonatology resources especially due to prematurity